The Effectiveness of Using Mobile Learning-Based E-Plantbook with a Scientific Approach to Increase Student Learning Outcomes - Maghfiroh, Maila Shofa; Rahayu, Enni Suwarsi; Widiatningrum, Talitha Widiatningrum (Universitas Negeri Semarang, 2023)
The use of learning resources that have not yet ideal creates difficulties for students, particularly on Plantae material at SMA Negeri 1 Kembang, Jepara Regency, Central Java Province. Students had difficulties in identifying, mentioning, explaining the characteristics, body structure, and grouping plants into divisions based on general characteristics. In addition, the absence of the data from observations and phenetic and phylogenetic analyzes of plants and the role of plants in survival on earth (particularly in the surrounding environment), had an impact on the difficulty of achieving Core Competency Plantae. This study aims to analyze the effectiveness of the e-plantbook with a scientific approach to student learning outcomes at SMA Negeri 1 Kembang, Jepara Regency, Central Java Province. E-plantbook is a mobile learning applications-based e-book naming on Plantae material. E-plantbook can be used as an alternative learning resource for students. This research method is quasi-experimental to measure the effectiveness of using e-plantbook with a non-equivalent research design pretest-posttest control group design to measure learning outcomes. The average of student learning outcomes in the cognitive aspect is 89. E-plantbook is assessed to be effective based on a) the results of the t test for increasing cognitive learning outcomes with a significance of 0.000 (< 0.05) which indicates a significant difference in learning outcomes between the experimental class and the control class, b) N Gain cognitive learning outcomes of 0.71 in the experimental class is greater than the control class (0.45), and c) the average score of the psychomotor aspect of the experimental class (3.80) with a very good category and greater than control class (3.53) with very good category. The use of e-plantbooks in the learning process could encourage student-centered learning because students were more active and students could learn independently.